Formulation of technology strategy for the Center for the Professional Advancement of Educators - Gonong, Eduard O.
The Center for the Professional Advancement of Educators (CPAE) is a partner-organization of the Department of Education (DepEd) with a vision of educators-led nation-building and development. They capacitate and empower educators in enriching and developing learners through the seminar-workshops that they conduct. In just their first year, they were able to serve around 4,000 educators and learners all over the Philippines.